2016
DOI: 10.3847/1538-4357/833/2/242
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Harmonic Analyses of Intensity Mapping Power Spectra

Abstract: Intensity mapping is a promising technique for surveying the large scale structure of our Universe from z = 0 to z ∼ 150, using the brightness temperature field of spectral lines to directly observe previously unexplored portions of out cosmic timeline. Examples of targeted lines include the 21 cm hyperfine transition of neutral hydrogen, rotational lines of carbon monoxide, and fine structure lines of singly ionized carbon. Recent efforts have focused on detections of the power spectrum of spatial fluctuation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 152 publications
0
40
0
Order By: Relevance
“…As pointed out by Vaughan et al (2016), our incomplete knowledge of quasar variability, in combination with the limited quality of the optical light curves can lead to false detections of periodicity. This was demonstrated in the case of the quasar PSO J3334.2028+01.4075 (Liu et al 2015), whose follow-up monitoring failed to show persistent periodicity (Liu et al 2016). In addition, Sesana et al (2017) calculated the GW background for the population of SMB-HBs implied by the identified periodic binary candidates, and found that it is in tension with the current upper limit derived from PTAs.…”
Section: Introductionmentioning
confidence: 87%
“…As pointed out by Vaughan et al (2016), our incomplete knowledge of quasar variability, in combination with the limited quality of the optical light curves can lead to false detections of periodicity. This was demonstrated in the case of the quasar PSO J3334.2028+01.4075 (Liu et al 2015), whose follow-up monitoring failed to show persistent periodicity (Liu et al 2016). In addition, Sesana et al (2017) calculated the GW background for the population of SMB-HBs implied by the identified periodic binary candidates, and found that it is in tension with the current upper limit derived from PTAs.…”
Section: Introductionmentioning
confidence: 87%
“…There have been a number of different proposed methods for estimating the cosmological PSP from interferometric measurements, including the imaging PS, the variance statistic, the delay spectrum, and m-mode analysis (Zaldarriaga et al 2004;Morales & Hewitt 2004;Mellema et al 2006;Stuart et al 2008;Iliev et al 2008;Chang et al 2008;Pen et al 2009;Vedantham et al 2012;Parsons et al 2012;Masui et al 2013;Switzer et al 2013;Patil et al 2014;Shaw et al 2014;Dillon et al 2014;Paul et al 2014Paul et al , 2016Trott et al 2016;Liu et al 2016;Gehlot & Koopmans 2017). While the language used to describe the estimators is highly variable, the mathematics fall into two families depending on whether they measure the PS of the measured visibilities ('delay spectrum' approaches) or the PS of the reconstructed sky ('imaging' PS approaches).…”
Section: Power Spectrum Estimatorsmentioning
confidence: 99%
“…where a m ℓ are the SH coefficients of the brightness temperature distribution. As discussed earlier by Shaw et al (2014Shaw et al ( , 2015 (and also by Zheng et al 2014;Zhang et al 2016a,b;Liu et al 2016), the visibilities can be expressed in terms of the SH coefficients a m ℓ as,…”
Section: Visibilities and Beam Transfer Functionsmentioning
confidence: 90%